(untitled) (Journal of Asian Development Studies, 2024)
Human capital refers to the literacy rate and life expectancy on total factor productivity (TFP). This analysis is based on how total factor productivity is affected by human capital in Pakistan. The study was conducted in Pakistan. The ARDL method, based on data from 1980 to 2017, is used to test this relationship. Results indicated that human capital (health) in terms of life expectancy positively and significantly impacts total factor productivity in Pakistan. The available evidence also suggests that the effect of health (life expectancy) on total factor productivity (TFP) is superior to the effect of education on literacy rate. The association between gross fixed capital formation (GFCF) is statistically significant, and their impact is positive on total factor productivity (TFP). The outcome also demonstrates that GDP and LR have insignificant associations with TFP. It is recommended that the Pakistani government spend more on human capital to enhance skills and become more productive. High educational funds should be allocated to promote education. Therefore, Pakistan must increase the quality of education in both the short and long- run to attain the higher total factor productivity growth.